(3GdJShjb GdeHGTQ ef NdGd bhGYO GdHjGfGJs - (3LQej(B, (3echQcds; (3NGdO GdYGeQj(B, s ((3GdbGgQI(B:s (3OGQ GdaGQhb(B,s, 2006)
(3GdJShjb aj YUQ bhGYO GdHjGfGJ, eaghe GdJShjb GdeHGTQ, eQGMd GdGROgGQ hGdGfMSGQ aj GdJShjb hGSY GdfWGb, GROgGQ GdJShjb GdbGFe Ydi GdHjGfGJ, JWHjbGJ GdJShjb GdeHGTQ, GfTGA hGSJNOGe fXe GdeYdheGJ GdJShjbjI, GdGgOGa hGdSjGSGJ GdJShjbjI GdgGOaI Gdi KbI GdYedGA, eYdheGJ egeI Yf bhGYO GdHjGfGJ, GLQGA GdGNJHGQGJ hGYOGO GdfeGPL hGdJcgf HGdfJGFL, GdGSJaGOI ef GdHjGfGJ aj eLGd GdJShjb, bGYOI ehMOI dcd ef GdeSJgdcjf hGdYedGA ef GdTQcGJ GdJLGQjI, HjGfGJ GdJShjb GdOhdj, GHMGK GdShb hLeY GdHjGfGJ hbVGjG GdNUhUjI, JcGed GdJShjb GdeHGTQ, GYOGO NWW GdJShjb GdeHGTQ, GYOGO ejRGfjGJ GdJShjb, cjajI GdGYOGO dNWW GdYed hGdGOGQI, GSGdjH GdJShjb GdeHGTQ, GgejI GSGdjH GdJhGUd GdJShjbjI hJWHjbGJgG, GdGSJLGHI GdeHGTQI(B: (3LPH GdeRjO ef GdYedGA, GdJNWjW GdGYdGej ddGSJLGHI GdeHGTQI, GdGNJHGQ GdeSJeQ dbje eYGedGJ GdYedGA, GdMaGX Ydi bGYOI GdYedGA, GdJhGUd hGdJaGYd eY GdYedGA, OQGSI MGdIs
Keywords: (3GdHjGfGJs; (3GdJShjbs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s